KAJIAN KETERAMPILAN BERPIKIR ANALITIS SISWA MELALUI MODEL PROJECT BASED LEARNING PADA KURIKULUM MERDEKA - Andarini, Silvia Yusiana; Utami, Ajeng Putri; Aprilia, Defi Nurdiana; Lesmono, Albertus Djoko (FKIP e-PROCEEDING, 2024)
ABTRACT Education in the 21st century plays a crucial role in facing the rapidly evolving era of globalization. It is expected that education in this century can be a tool to increase human knowledge. In 21st-century learning, analytical thinking skills are essential in the learning process. This research aims to review the results of several primary studies on analytical thinking skills. A Systematic Literature Review (SLR) was used as the method in this research, through a search in the Google Scholar database from 2019 to 2024, resulting in 8 primary research articles that met the predetermined inclusion criteria. Each article was recorded and then classified based on the title, year of study, and results to be analyzed one by one. The results of this study show that students' analytical thinking skills improved with the use of the PjBL model. This is because, in PjBL, learning is student-centered, allowing students to be more actively involved in the learning process, independently explore information, and develop critical and analytical thinking skills. Additionally, PjBL encourages students to collaborate in solving real-world problems, thereby strengthening their skills in analyzing situations and finding innovative and relevant solutions. Keywords : Analytical Thinking, Project-Based Learning, Independent Curriculum